Simultaneous occurrence of cutaneous melanocytic neoplasia in Duroc and German Saddleback pigs from three smallholder farms - Thies J. Nicolaisen; Melanie Stoff; Manon Mikic; Anna Lena Maschmeier; Johannes Buchallik-Schregel; Alexandra von Altrock; Maybrit Wirtz; Saskia Neubert; Andreas Beineke; Doris Höltig; Isabel Hennig-Pauka; Martin Ganter (BMC Veterinary Research)
Abstract Background Congenital melanocytic neoplasia is a rare disease that is described for the pig breeds Duroc, Iberico and Nero Siciliano used in agriculture. The hereditary nature of this neoplastic condition has been substantiated. The clinical course is unpredictable, spanning from complete spontaneous regression of primary tumors and survival of afflicted animals to a fatal progression marked by metastases to internal organs. In contrast to other species, no clinical or histological prognostic criteria for assessing the clinical course of disease exist in pigs. Case presentation Four cases of cutaneous melanocytic neoplasia are described that occurred concurrently in three small-scale farms in northwestern Germany in 2023. These cases underwent thorough diagnostic evaluation employing a spectrum of modalities including clinical examination, hematological analysis, pathohistological examination, X-ray imaging, broncho-alveolar lavage, computed tomography, and autopsy. The first and the second case deal with two Duroc crossbred littermates with divergent courses of disease: While the black colored piglet had to be euthanized at eight weeks of life due to widespread metastases affecting multiple organs, the neoplastic disease remained localized to the primary tumor in the red-brown colored pig. Broncho-alveolar lavage was utilized in the black colored piglet to identify metastatic lesions of the melanoma within the lung tissue. The third case represents the initial observation of an affected Duroc gilt manifesting generalized leukoderma and leukotrichia during the regression phase of the cutaneous melanocytic tumor. The first observation of a congenital melanoma in a German Saddleback (variety: Husum Red Pied) is described in the fourth case. Notably, the primary tumor exhibited regression over the course of the disease. Conclusion A higher incidence of this neoplastic disease can be assumed for small-scale farms in northwest Germany compared to professional pig husbandry due to potential inbreeding. No epidemiological or family link could be found between the two cases of affected Duroc pigs. Notably, the endangered Husum Red Pied breed maintains a limited genetic diversity, emphasizing the imperative of integrating considerations of this disease into breeding programs to mitigate the heightened risk of hereditary neoplastic afflictions in subsequent generations.